LEGAL CERTAINTY OF THE USE OF CRYPTOCURRENCY AS A PAYMENT INSTRUMENT FROM THE PERSPECTIVE OF INDONESIAN POSITIVE LAW - Wahyudi, Bambang Tresno; Dewi, Nourma; Suniaprily, Firstnandiar Glica Aini (Awang Long Law Review, 2026)
This study aims to provide answers to the legal certainty provided by laws and regulations regarding the use of cryptocurrency as a payment instrument in Indonesia and efforts to achieve legal certainty for the use of cryptocurrency as a payment instrument in the future. Cryptocurrency is an impact of globalization that must be responded to with legal changes, given the large amount of its global use that has an impact in Indonesia. The Currency Law does not explicitly provide space for cryptocurrency, implicating limited regulatory space for its use in Indonesia. A study analyzing the guarantee of legal certainty for cryptocurrency use is needed in light of existing normative regulations and efforts to achieve such legal certainty. This research is normative with a legislative and conceptual approach. The results show that the form of legal certainty in laws and regulations regarding the use of cryptocurrency as a payment instrument in Indonesia is not yet regulated in Law Number 7 of 2011 concerning Currency, but cryptocurrencies are partially regulated as commodities that can be traded on futures exchanges, in accordance with Minister of Trade Regulation Number 99 of 2018 concerning General Policy for the Implementation of Crypto Asset Futures Trading. This means that cryptocurrencies cannot yet be used as payment instruments but have limited transaction value on futures exchanges. Efforts to realize legal certainty for the use of cryptocurrency as a payment instrument in the future include injecting cryptocurrency as a digital payment instrument into Law Number 7 of 2011 concerning Currency, formulating technical regulations for the Regulation of the Minister of Trade and Bank Indonesia Regulations that accommodate the technical procedures for the use of cryptocurrency, and with the recognition of cryptocurrency in the updated Currency Law, its use can be guaranteed at the Deposit Insurance Corporation.